2021
DOI: 10.3389/fphys.2021.649282
|View full text |Cite
|
Sign up to set email alerts
|

Sub 3-Hour Marathon Runners for Five Consecutive Decades Demonstrate a Reduced Age-Related Decline in Performance

Abstract: Estimation of the age-related decline in athletic performance by analyzing age-group world record performances presents an inherent limitation because the records generally belong to different individuals. Longitudinal studies describing the changes in performance with advancing age for the same individuals with a consistent training regimen are more appropriate to determine age-related changes in performance. The aim of this longitudinal study was to examine the age-related decline in running performance of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…His decline in marathon performance between 51 and 71 years old (from 2:41 to 2:54) corresponds to an 8% reduction in running speed in 20 years (4% per decade). This age-related performance decline is lower than the 5%-7% per decade generally observed for well-trained marathoners (Lepers et al, 2020;Lepers et al, 2021). Note that the athlete used short (e.g., 10 min) powernaps between two sessions on the same day, but did not apply periodization, did not follow a special diet, and did not perform any heavy resistance training.…”
Section: Discussionmentioning
confidence: 78%
“…His decline in marathon performance between 51 and 71 years old (from 2:41 to 2:54) corresponds to an 8% reduction in running speed in 20 years (4% per decade). This age-related performance decline is lower than the 5%-7% per decade generally observed for well-trained marathoners (Lepers et al, 2020;Lepers et al, 2021). Note that the athlete used short (e.g., 10 min) powernaps between two sessions on the same day, but did not apply periodization, did not follow a special diet, and did not perform any heavy resistance training.…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that most endurance athletes experience a decrease in their athletic performance with increase in age, including a reduction in cardiovascular function due to a loss of muscle mass (Fleg and Lakatta, 1988), a lower maximal heart rate, cardiac output, arteriovenous oxygen differences and maximal aerobic capacity (Fleg and Lakatta, 1988;Wilson and Tanaka, 2000;Pantoja et al, 2016;Willy and Paquette, 2019;Valenzuela et al, 2020). However, a longitudinal observation of endurance runners spanning over five decades demonstrated that training and racing may limit the reduction in performance to 7% per decade (Lepers et al, 2021). Taken together, the present findings suggest that hill running may be beneficial for maintaining aspects of cardiorespiratory fitness that would otherwise be negatively affected by ageing.…”
Section: Discussionmentioning
confidence: 99%